Sound Bite Effect dalam Komunikasi Politik - Ritonga, Muhammad Husni (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2019)
The political year has seemed to be moving so fast. The 2019 Presidential General Elections in Indonesia gave rise to various political communications in order to attract public sympathizers. At the time, political contestation was often associated with a variety of utterances which in the end provoked conflict so that politics in the country was more interesting to study, especially in the study of political communication. All remarks conveyed by political communication figures are considered as interesting things to study. Various kinds of utterances, speeches or statements can in fact have an effect on the interlocutor so that the messages of political communication are considered to have certain symbols, both verbally and non-verbally. Nevertheless, political communication delivered by political actors can actually have an extraordinary effect on political opponents. Not just words, even body gestures can become weapons of political messages that can have an effect on political opponents. This paper discusses political symbols, such as speech or body gestures that can have an extraordinary effect on political opponents. All was done to attract public interest in one of the candidates for the President of the Republic of Indonesia, especially in the context of the 2019 General Elections..Keywords: Political Messages, Sound Bite, Political News Tahun politik terasa bergerak begitu cepat. Pemilihan Umum (Pemilu) calon Presiden yang dilaksanakan tahun 2019 memunculkan berbagai komunikasi politik demi menarik simpatisan masyarakat. Pada masa itu, kontestasi politik sering dikaitkan dengan berbagai macam ucapan yang pada akhirnya memancing konflik sehingga perpolitikan di tanah air semakin menarik untuk dikaji, khususnya dalam kajian komunikasi politik. Segala ucapan yang disampaikan oleh para tokoh komunikasi politik dianggap sebagai suatu hal yang menarik untuk dikaji. Berbagai macam ucapan, ujaran ataupun pernyataan nyatanya bisa memberikan efek terhadap lawan bicara sehingga pesan-pesan komunikasi politik dianggap mempunyai simbol-simbol tertentu, baik secara verbal maunpun non-verbal. Kendati demikian, komunikasi politik yang disampaikan oleh para aktor politik ternyata bisa memberikan efek yang luar biasa terhadap lawan politik. Bukan hanya sekadar ucapan, bahkan gestur tubuh pun bisa menjadi senjata pesan politik yang dapat memberikan efek kepada lawan politik. Tulisan ini membahas simbol-simbol perpolitikan, seperti ucapan ataupun gesture tubuh yang bisa memberikan efek yang luar biasa kepada lawan politik. Semua itu dilakukan untuk menarik minat masyarakat terhadap salah satu pasangan calon Presiden Republik Indonesia, khususnya dalam konteks Pemilihan Umum (Pemilu) 2019.Kata Kunci: Pesan Politik, Sound Bite, Berita Politik